LinkAja Business Models Strategy Development Using BMC Approaches - Novreyna Ludmilla Alda; Sari Wulandari (School of Industrial and System Engineering, Telkom University, 2020)
In the first quarter of 2019, there was an increase in the value and the volume transaction on electronic money transactions in Indonesia. The development of electronic money is directly proportional to the high competition of companies engaged in the field of mobile payment. LinkAja is a mobile payment application product that is representative of collaboration between Telkomsel and the number of State-Owned Enterprises (SOEs). One of the keys to success in facing competition is to develop continuously. Therefore, it is necessary to develop the right business model to determine the optimal strategy in developing the LinkAja application business. The objectives of this research are formulating and developing LinkAja business models strategy. This result of this study proposed business model in the form of improvement for each element of its business model including: elements (1) Customer segments: Adding target customers to e-marketplaces and e-commerce, (2) Customer relationships: Developing cooperation with LinkAja competitors, (3) Value Proposition: Developing customer consulting services by providing training for using the LinkAja application, (4) Key Activities: Developing collaboration with partners and competitors, (5) Key Partners: Collaborating with the competitors such as Gopay, OVO, FUND, etc., (6) Key Resources: Using digital budget information systems to facilitate transparency of company budgets, (7) Revenue streams: Upgrading fees for premium services, and (8) Cost Structure: Research costs.